TINJAUAN YURIDIS TERHADAP KEABSAHAN SUATU PERJANJIAN OLEH PARA PIHAK YANG MENGAKIBATKAN WANPRESTASI (PUTUSAN NO.336/PDT/2014/PT.MDN) - Atika Atika Sirait; Nova Nova Sherly; Tiopan Tiopan Aritonang; Roby C Sianturi (Ilmu Hukum Prima (IHP), 2019)
Article 1338 BW states that agreements must be carried out in good faith. But in the case of this decision, the Defendant I did not have a good intention in the agreement. Opponents defaulted on the Opponents by lending money and not returning it according to the agreed time. A few months later, Defendant I wanted to pay off his debt by giving 2 blank checks as a fulfillment of the promise of the agreement and it turned out that it could not be disbursed / rejected by the bank. The purpose of this study is, (a) to find out that the agreement made by the Opponents and the Defendant I is legal or not in accordance with applicable laws; (b) in order to know the legal consequences of breach of the validity of the agreement between the Opponent and the Defendant I; (c) in order to find out the name of the deed of sale and purchase in that case is legal or not in accordance with the applicable law. The method used in this study is a normative juridical method. The results of this study indicate that (a) the agreement made by the Opponents and the Defendant I has fulfilled the legal requirements of the agreement but the Defendant is in default; (b) the legal consequences that should be received by the Defendant in accordance with Article 1243 BW are obliged to pay compensation suffered by the Defendant; (c) turning the name of the certificate should not be valid because of the cancellation of the agreement on the default made by the Defendant I against the Opponent.